2021
DOI: 10.18203/2320-6012.ijrms20213946
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine versus dexamethasone as adjunct to ropivacaine in erector spinae plane block for patients undergoing breast surgery: a randomized, prospective, double blinded study

Abstract: Background: Loco-regional anaesthesia (GA) has been extensively applied in the clinical field for achieving post-operative analgesia. Erector spinae plane block (ESPB) which is a novel inter-fascial plane block has been widely used for breast surgery. Dexmedetomidine and dexamethasone as an adjunct to local anaesthesia have been widely reported to reduce postoperative pain and analgesic consumption but there are no studies comparing both these drugs in ESPB for breast surgery.Methods: Sixty ASA I-II patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…However, Basing et al (17) results were not similar to ours. They conducted a study comparing dexmedetomidine and dexamethasone as additives to ropivacaine in erector spinae plane block for patients undergoing breast surgery and concluded that p value was > 0.05% between the 2 groups in their statistical analysis of VAS at different time points with median was 2 in both groups.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…However, Basing et al (17) results were not similar to ours. They conducted a study comparing dexmedetomidine and dexamethasone as additives to ropivacaine in erector spinae plane block for patients undergoing breast surgery and concluded that p value was > 0.05% between the 2 groups in their statistical analysis of VAS at different time points with median was 2 in both groups.…”
Section: Resultscontrasting
confidence: 85%
“…However Margulis et al (31) and Basing et al (17) contradict our results where they found that intraoperative opioid consumption was less in the dexmedetomidine group when compared to both the control and dexamethasone group when both drugs were used as adjuvant to (20) ml ropivacaine 0.5% in ultrasound guided interscalene block in arthroscopic shoulder surgery and there was no difference in total analgesic consumption and the demand for first rescue analgesia between the dexmedetomidine and dexamethasone group in their comparative study between dexmedetomidine and dexamethasone as adjunct to ropivacaine in erector spinae plane block for patients undergoing breast surgery respectively. This may be due to lower dexamethasone dose (4mg) in the 1st study and difference in dexmedetomidine dose they used (0.5ug/kg) in 2nd one.…”
Section: Resultsmentioning
confidence: 99%